Strategies to Optimize Antiplatelet Effects and Minimize Bleeding in NSTE-ACS - Rizzo, Toni (MD Conference Express, 2014)
Patients with non-ST-elevation (NSTE) acute coronary syndrome (ACS) are treated with antiplatelet and anticoagulation to reduce ischemic complications [Hamm CW et al. Eur Heart J 2011; Wright RS et al. J Am Coll Cardiol 2011]. This article discusses selecting the appropriate therapies and improving short- and long-term outcomes in patients with NSTE-ACS.